Body-Size Change in a Rodent Is Affected by Environmental Warming and Population-Specific Thermoneutral Zone - Yan Chen; Ke Li; Stefan Sommer; Arpat Ozgul; Yizhen Zhang; Deng Wang (Animals)
Rodent body size often exhibits a diversity of temperature–size patterns among and within species, which might be caused by differential thermoneutral zones (TNZs) and experienced extents of warming. Here, we test this hypothesis in populations of Apodemus agrarius. To study how body size varies across space, we analysed data on body size and temperature (specifically, annual mean minimum temperature) from nine sites spanning 1150 m of elevation. Using indirect calorimetry, we also measured the resting metabolic rate at different temperatures to infer the population-specific TNZ. To study how body size changes over time (2013–2020), we analysed body-size data of southern and northern populations from warm and cold sites, respectively. With increasing temperatures across space, body size increased and the TNZ narrowed. Moreover, during the eight years, temperature remained stable at the warm site but rose at the cold site. As a result, body size increased in the population at the cold site but remained stable in the population at the warm site. Finally, the rate of change in body size per 1 °C change in temperature was larger along the temporal than the spatial temperature gradient. Together, these results support our hypothesis that, among rodent populations, differential changes in body size can be caused by site-specific habitat warming and the population-specific TNZ. A population with a narrow TNZ can be restricted in its body-size response to habitat warming.